THE ANTIDIPHTHERIA ANTIBODIES OF SEROEPIDEMIOLOGY SURVEY AMONG ADOLESCENTS IN BANGKALAN AND KEDIRI DISTRICTS - Dominicus Husada; Kristina Marbun; Desy Primayani; Leny Kartina; Dwiyanti Puspitasari; Parwati Setiono Basuki; Ismoedijanto Moedjito; Aris Wiji Utami; Eveline Irawan (Jurnal Berkala Epidemiologi, 2019)
Background: An increase in diphtheria cases has occurred in East Java Province since 2011. The resistance level to diphtheria is considered as the most important cause. Purpose: The study aims analyzed the immunity level immunity to diphtheria in adolescents aged 16-18 years old in Bangkalan and Kediri Districts. Methods: This study was a cross-sectional study, conducted on students in eleven grade of senior high schools (SMAN) from both districts. The inclusion criteria included being 16-18 years old and students in eleven grades of senior high schools in Bangkalan and Kediri. This study was approved by their parents/guardians. The exclusion criteria included immunocompromised students and those who have a history of diphtheria infection. The data were obtained from 204 samples, 89 samples in Bangkalan, and 115 samples in Kediri. The antidiphtheria antibodies examination was carried out by the Vero cell method. The antibodies levels were grouped according to WHO standard, consist of vulnerable, basic, full, and long-term. Further analysis was done with 2 tiers of immunity, consist of immune and vulnerable. Results: The immunization coverage for basic and booster diphtheria vaccine is better in Kediri than in Bangkalan. In contrast, levels of antibodies samples in Bangkalan District is better. The participants who were immune in Bangkalan were higher than those in Kediri (91% vs. 44.3%). Conclusion: The immunity adolescents of Bangkalan is higher than in adolescent Kediri District. The adolescents in Kediri have a greater risk to get infected by the disease